METODE YURIDIS PENGELOLAAN SAMPAH RUMAH TANGGA DAN SAMPAH SEJENIS DI STT-PLN - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2018)
This paper uses exploratory research to conduct research in Final Disposal Site and Waste Management STT-PLN Jakarta. Keep questioning and interviewing students and officers at Final Disposal. The research team is also on reference books, research results and national journals and legislation discussing with waste management. The problem in this paper is dilipatbelangi with increasingly creating the number of Indonesian population until in 2011 reached 259,940,857 people who cause people who do business to produce works of real standard of living that has a positive and negative impact. Negative impact on the environment is very prominent problem of pollution. The most common contamination is garbage. Therefore, agar-agar can help the tasks in the necessary and very high effective difficulties in handling waste and vice versa, the efforts required will produce even more. To achieve the things necessary for proper ways and technologies and from waste sources. In addition, it also needs legal aspects to be a Guidebook-Regulations related to waste and the environment in order to cope with environmental pollution caused by garbage.